The Role of Professional Learning in Addressing Global Challenges: Tensions and Innovations Associated With AMR - Littlejohn, Allison; Charitonos, Koula; Kaatrakoski, Heli (Frontiers in Education, 2019)
This study examines ways in which technology-enhanced, professional learning can be considered a driving force for the capacity building needed to solve global challenges. The work is contextualized within the global health challenge of Antimicrobial Resistance (AMR) and examines how an AMR surveillance system is being set up in a low-to-middle-income country in Asia (Country A). The research interrogates forms of technology-supported professional development that can expand the work practices of professionals. Technology-Enhanced Learning (TEL) research frequently takes a design perspective, where learning activities are designed around knowledge objectives and the learning is then applied to the workplace. This research takes an original standpoint by placing attention on specific work practices, then examining how technology-supported activities can build capacity. The research places professionals at the centre of a critical approach examining the ways technologies can add value to their professional lives. This method highlights the importance of the professionals’ “voice” as a lens through which researchers document their reality. The study calls for a fundamental shift in the orientation of research in Technology Enhanced Learning, moving attention towards work practice and mapping supporting technologies around this, rather than focusing primarily on the technology and planning learning activity with technology tools.